2016
DOI: 10.1590/1980-5918.029.004.ao03
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of patients with multiple sclerosis according to tests of the Multiple Sclerosis Functional Composite

Abstract: Introduction: The Multiple Sclerosis Functional Composite (MSFC) is a scale that evaluates the functional

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
(31 reference statements)
0
3
0
3
Order By: Relevance
“…Dentre as revistas, a área de medicina recebeu maior porcentagem, sendo que 16 tinham enfoque na neurologia, 2 revistas eram específicas sobre EM e outras 2 sobre doença autoimune de forma geral. Nenhuma revista brasileira foi identificada que se dedique apenas para EM, mas duas revistas brasileiras apareceram na lista com artigos sobre o tema: Arquivos de Neuro-Psiquiatria e Fisioterapia em Movimento (Caneda, Vecino, 2016;Figueiredo, Polachini, & Prado, 2016). Arquivos de Neuro-Psiquiatria é publicado pela Academia Brasileira de Neurologia e a revista Fisioterapia em Movimento pela Pontifícia Universidade Católica do Paraná.…”
Section: Resultsunclassified
“…Dentre as revistas, a área de medicina recebeu maior porcentagem, sendo que 16 tinham enfoque na neurologia, 2 revistas eram específicas sobre EM e outras 2 sobre doença autoimune de forma geral. Nenhuma revista brasileira foi identificada que se dedique apenas para EM, mas duas revistas brasileiras apareceram na lista com artigos sobre o tema: Arquivos de Neuro-Psiquiatria e Fisioterapia em Movimento (Caneda, Vecino, 2016;Figueiredo, Polachini, & Prado, 2016). Arquivos de Neuro-Psiquiatria é publicado pela Academia Brasileira de Neurologia e a revista Fisioterapia em Movimento pela Pontifícia Universidade Católica do Paraná.…”
Section: Resultsunclassified
“…Due to the diffuse character of the formation of the demyelinating plaques, the symptoms and presentations are determined by the location of the lesions [2]. The high variability of the symptoms has been reported that their persisting during the disease course leads to clinically significant symptoms such as changes in muscle tone, muscle weakness, motor incoordination, and postural errors [3].…”
Section: Introductionmentioning
confidence: 99%
“…The high variability of the symptoms has been reported that their persisting during the disease course leads to clinically significant symptoms such as changes in muscle tone, muscle weakness, motor incoordination, and postural errors [3]. These changes may limit MS patients in the performance of their daily activities, as well as has a negative influence on social life [2,3]. Nowadays, the majority of clinicians and researchers agree that combining both pharmacologic and nonpharmacological treatments can manage the disease adequately [4].…”
Section: Introductionmentioning
confidence: 99%
“…2020, v. 46, n. 2: e55384 Efeitos do ziclague na espasticidade e seu impacto sobre a força muscular e cinemática da marcha: estudo de caso INTRODUÇÃO A Esclerose Múltipla (EM) é uma patologia inflamatória autoimune, que se caracteriza por lesões desmielinizantes do Sistema Nervoso Central (SNC). É de caráter progressivo, possui períodos de remissão e exacerbação dos sintomas e a sua etiologia é desconhecida 1 . As manifestações clínicas variam de acordo com a área da lesão, podendo ocorrer alterações motoras, sensitivas e cognitivas 1,2 .…”
unclassified
“…É de caráter progressivo, possui períodos de remissão e exacerbação dos sintomas e a sua etiologia é desconhecida 1 . As manifestações clínicas variam de acordo com a área da lesão, podendo ocorrer alterações motoras, sensitivas e cognitivas 1,2 .…”
unclassified